The Mediating Role of Smartphone Usage in the Relationship Between Working Mothers and Children’s Social Interaction - Saroinsong, Wulan Patria; Nursalim, Mochamad; Nor, Azmawaty Binti Mohamad (Jurnal Kajian Bimbingan dan Konseling, 2025)
This study explores how smartphone usage acts as a mediator in the connection between working mothers and social interaction among children aged 3–6 years in East Java, Indonesia. Due to the insufficient reading and writing skills of children in this age range to complete questionnaires for the children’s interaction variable, data were gathered from their parents’ perspective, notably working mothers, who offered insights into their parenting behaviors and their children’s interaction patterns when using the smartphone. The research utilized a mediation analysis design to examine the relationships among the variables. A structured questionnaire was distributed to a sample of 400 working mothers chosen through purposive sampling. Data were subjected to path analysis, with Hayes’s PROCESS Model 4 applied to examine mediation effects. The results revealed a substantial negative correlation between the smartphone usage (M) of working mothers and the social interactions of their children. Furthermore, smartphone usage was identified as a mediator in the association between working mothers and children’s social interaction, indicating that heightened dependence on smartphones by mothers may indirectly diminish the quality of parent-child interactions and children’s interaction with peers. These findings highlight the significance of intentional technology utilization in parenting, particularly for working mothers managing professional and caregiving responsibilities.